Prognostic Significance of MGMT Promoter Methylation in Egyptian GBM Patients: A Single-institution Experience - Abdel Moneim, Rabab; Abdel-Rafei, Mohamed; Hassan, Hesham; El-Zawahry, Ibrahim; Bassam Hashem, Wedad (Asian Pacific Journal of Cancer Biology, 2018)
Background: Glioblastoma Multiforme (GBM) is the highest-mortality tumor of the central nervous system. Epigenetic silencing of the MGMT gene by promoter methylation is associated with loss of MGMT expression and deficiency in MGMT-mediated DNA repair, which is affiliated with improved survival in patients treated with alkylating agents such as TMZ. Purpose: This is a retrospective work, studying the MGMT promoter status in a group of GBM patients; correlating this status to time to progression (TTP) and overall survival (OS). Methods: Thirty-nine patients with GBM, treated in Kasr El-Ainy Center of Clinical Oncology and Nuclear Medicine (NEMROCK) between January 2014 and January 2015, were included in our study. The QIAamp DNA FFPE Tissue Kit (Qiagen, USA) was used for genomic DNA extraction from Formalin-fixed paraffin-embedded tumor tissues of the 39 patients. Bisulfite modification of DNA was performed for detecting methylation in MGMT promoter using EpiTect Bisulfite Kit (Qiagen, USA). Specific primers were used to match methylated & un-methylated DNA that was visualized by loading its PCR products in gel electrophoresis system. All statistical analyses were carried out using SPSS version 20.0. Results: The mean age for our patients was 48 years; with a male to female ratio of 1.3:1. MGMT promoter methylation was found in 27 patients (69.2%) compared to 12 (30.8%) with un-methylation. TMZ was received in 71.8 % (28) of our patients throughout their treatment. The median OS for all patients was 20.03 months; while the median TTP 15.03 was months. Although the OS was statistically significantly higher for patients with the methylated promoter (p-value = 0.004) compared to the un-methylated group; yet the TTP difference did not reach a statistically significant value (p-value = 0.048). Conclusions: The epigenetic silencing of the MGMT gene by promoter methylation has been associated with longer OS & TTP in patients with GBM.